Aspects of opening play - Apimuk Muangkasem; Hiroyuki Iida; Kristian Sporer (Penerbit Universiti Kebangsaan Malaysia, 2013)
In this paper, we study opening play in games. We show experiments using minimax and a semi-random player. In the experiment, we let each semi-random player use an opening-book, created by different player. Results show evidence for the following statements. The game length increases. Expert player against an intermediate player should not use an opening book in a tournament match. Some opening books are good for novices and some opening books are bad for novices. The game outcome will approach the outcome of the game when the opening book was created, and if a grandmaster creates the opening book then the outcome will be the same as the grandmaster’s.